Hypertension and physical activity in middle-aged and older adults in China. Issue 1 (December 2018) - You, Yinghui; Teng, Wenjie; Wang, Jincai; Ma, Guifeng; Ma, Anning; Wang, Junjie; Liu, Pengtao
Abstract There are few studies examining the association between levels of physical activity and hypertension in middle-aged and older adults in China. Data were drawn from the Chinese Health and Retirement Longitudinal Study (using four-stage stratified probability-proportional-to-size sampling), involving 7113 individuals aged 45 years and older from 28 provinces of China. Hypertension was defined as a systolic BP ≥ 130 mm Hg, or diastolic BP ≥ 80 mm Hg, or self-reported use of anti-hypertensive medications. The awareness, treatment, and control among hypertensive participants were 53.12%, 43.37%, and 10.03%, respectively. The prevalence of hypertension was 56.12% among all the participants, higher in main city zones (58.68%) than villages (55.52%) and other areas (55.78%, p < 0.0001). Participants who were overweight (BMI ≥ 24: AOR 4.08, 95% CI 3.21–5.20, P < 0.0001; BMI ≥ 28: 10.03, 7.56–13.31, P < 0.0001), and drinking more than once a month (1.28, 1.12–1.46, P < 0.0001) were more likely to have hypertension. The decision tree model was established to analyze the importance of different levels of physical activity on hypertension prevention. Participants who usually participated in moderate-to-vigorous activity for more than 10 minutes (vigorous: 0.82, 0.73–0.91, P = 0.0004; moderate: 0.83, 0.75–0.92, P = 0.0006) were less likely to have hypertension. The results of the decision tree showed that the vigorous physical activity seemed to be more important than moderate and light activity to induce beneficial effects on prevention of hypertension. The strength of our study is in using the decision tree to clearly rank the importance of those key factors affecting hypertension.